Comparative Effectiveness of Video and Leaflet Education on Nurses' Attitudes and Compliance with Standard Operating Procedures - Ahmad Fuad; Kusbaryanto Kusbaryanto (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Nurses’ compliance with Standard Operating Procedures (SOPs) is essential for ensuring patient safety and quality of care. Educational media are commonly used to improve nurses’ attitudes and compliance; however, evidence comparing the effectiveness of video and leaflet media remains limited. This study aimed to compare the effectiveness of video and leaflet education in improving nurses’ attitudes and compliance with SOPs. Method: A quasi-experimental study with a pretest-posttest two-group design was conducted among 60 nurses. Participants were divided equally into a video group (n=30) and a leaflet group (n=30). Data were collected using an attitude questionnaire and a compliance observation checklist. Following a single educational intervention, posttests were conducted 60 days later. Data were analyzed using the Wilcoxon Signed-Rank Test and the Mann-Whitney U test based on N-Gain scores. Result: Both groups showed significant improvements in attitudes and compliance after the intervention (p<0.001). The video group achieved higher N-Gain scores for attitude (79.11%) and compliance (77.43%), which were categorized as effective. The leaflet group achieved N-Gain scores of 66.97% for attitude and 71.88% for compliance, indicating moderate effectiveness. Significant differences were found between the two groups for attitude (p=0.008) and compliance (p=0.013), demonstrating that video-based education was more effective than leaflet-based education. Conclusion: Both video and leaflet education improved nurses’ attitudes and compliance with SOPs. However, video-based education produced greater improvements and may be recommended as a primary educational strategy to enhance nursing practice and patient safety.